2015
DOI: 10.2147/ott.s80255
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 rs153109 polymorphism increases the risk of colorectal cancer in Chinese Han population

Abstract: IL-27, a new member of the IL-12 family, has been found to have antitumor effects in colorectal cancer (CRC); therefore, polymorphisms of this protein may modulate CRC carcinogenesis. So, we studied the association of single nucleotide polymorphisms of the IL-27 gene with the risk of CRC occurrence using a case–control using 600 CRC patients and matched healthy controls. The IL-27 rs153109 polymorphism was analyzed with polymerase chain reaction-restriction fragment length polymorphism and DNA sequencing metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These findings suggested that IL-27 may lose its tumor suppressive role, which also provides an explanation for the high serum levels of IL-27 in the patients with CRC. A previous study revealed that the IL-27 polymorphism is associated with a high risk of CRC ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that IL-27 may lose its tumor suppressive role, which also provides an explanation for the high serum levels of IL-27 in the patients with CRC. A previous study revealed that the IL-27 polymorphism is associated with a high risk of CRC ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, IL-27, a member of the IL-12 cytokine family, has demonstrated antitumor activity via stimulation of cytotoxic T cells and natural killer cell function, regulating the differentiation of T cell subsets, and suppressing dendritic cell function and angiogenesis ( 16 ). In addition, IL-27 gene polymorphisms have been revealed to increase the risk of CRC development ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined the association between DOI:10.31557/APJCP.2020.21.9.2507 IL-27 polymorphisms and the risk of various cancer (Wei et al, 2009;Zhao et al, 2009;Guo et al, 2012;Huang et al, 2012;Pan et al, 2012;Tao et al, 2012;Peng et al, 2013;Munretnam et al, 2014;Tang et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Lyu et al, 2015;Pu et al, 2015;Zhang et al, 2015;Zhou et al, 2015;Ge and Xiao, 2016;Wang et al, 2016;Yu et al, 2016;Nie et al, 2017;Ghavami et al, 2018). The findings were controversial, though it is difficult to clarify the inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that IL-27 possesses antitumor activities against a variety of tumor types (Nagai et al, 2010;Di Carlo et al, 2014;Yoshida and Hunter, 2015;Yoshimoto et al, 2015). IL-27 is a polymorphic gene and several studies examined the association between IL-27 gene polymorphisms and risk of various cancers including, non-small-cell lung cancer (NSCLC) (Ge and Xiao, 2016), acute lymphoblastic leukemia (ALL) (Ghavami et al, 2018), nasopharyngeal carcinoma (NPC) (Wei et al, 2009;Pan et al, 2012), colorectal cancer (CRC) (Guo et al, 2012;Huang et al, 2012;Lyu et al, 2015), prostate cancer (PCa) (Munretnam et al, 2014), papillary thyroid carcinoma (PTC) (Zhang et al, 2015;Nie et al, 2017), hepatocellular carcinoma (HCC) (Peng et al, 2013), renal cell carcinoma (RCC) (Pu et al, 2015), osteosarcoma (Tang et al, 2014), esophageal cancer (Tao et al, 2012), cervical cancer (Wang et al, 2016), endometrial cancer (Yu et al, 2016), ovarian cancer (Zhang et al, 2014b), breast cancer (Zhang et al, 2014a), glioma (Zhao et al, 2009), and bladder cancer (Zhou et al, 2015). However, the findings of these studies have been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, relationships between polymorphisms and cytokine levels, including those of TGFβ1 and IL-10, -22, and -27, have been reported in CRC patients. [14][15][16][17] However, the effects of these cytokine gene polymorphisms on CRC patients in Saudi Arabia are understudied. The present study aims to explore how CRC patients in Saudi Arabia are affected by the presence of several specific cytokine polymorphisms: IL-8 (rs4073 T/A), IL-10 (rs1800896 A/G), IL-22 (rs1179251 C/G and rs2227485 C/T), IL-27 (rs17855750 T/G), and TGFß1 (rs1800469 C/T).…”
mentioning
confidence: 99%